A checklist of Scoliidae (Insecta: Hymenoptera) from China - Liu, Zhen; van Achterberg, Cornelis; He, Jun-Hua; Chen, Xue-Xin (Zootaxa, 2021)
A checklist of all confirmed species of the family Scoliidae (Hymenoptera) from China is made based on the Chinese specimens in the Naturalis Biodiversity Center (RMNH, Leiden) and on additional specimens from the Chinese Academy of Insect Science (IOZ, Beijing), the Zhejiang University (ZJUH, Hangzhou), and the Sun Yat-sen University (SYSUBM, Guangzhou). The Scoliid species from China belong to one subfamily, two tribes, 11 genera and 52 species. Two species are deleted from the fauna of China: Campsomeriella ilanensis (Tsuneki, 1972) and Scolia (Discolia) quadripustulata Fabricius, 1782. One subspecies, i.e., Carinoscolia vittifrons nipponensis Uchida, 1933, status nov., is elevated to species rank. Scolia (Discolia) formosicola Betrem, 1928, status nov. and S. (D.) inouyei Okamoto, 1924 are re-instated valid species.